Calcium ion-sensor based on polyindole-camphorsulfonic acid composite - Pandey P.C.; Chauhan D.S.; Prakash R. (My University, 2025)
We hereby report a new conducting polymer-based calcium ion exchanger, namely polyindole-camphorsulfonic acid (PIn-CSA) composite, and its application in the development of calcium ion-selective electrode. The processable PIn-CSA composite is developed by homogenizing equimolar ratio of chemically synthesized PIn and CSA in tetrahydrofuran. The homogenized PIn-CSA composite is cast over the Pt disc electrode under ambient conditions. The ion-sensor exhibits near Nernstian response for Ca 2+ over a concentration range of 2 × 10 -5 to 1 × 10 -2 M with a response time of 8 s. The sensor can be used for a period of over 3 months without any major drift in its baseline potential. The useful pH range of the ion-sensor was found out to be 4.0-8.0. © 2012 Wiley Periodicals, Inc.